Three-dimensional (13)C-spectroscopic imaging in the isolated infarcted rat heart. - Weidensteiner, C; Lanz, T; Horn, M; Neubauer, S; Haase, A; von Kienlin, M (2000)
Acquisition weighted (13)C-spectroscopic imaging with three spatial dimensions is demonstrated in the isolated, perfused rat heart. Experiments were performed at 11.75 T with a home-built double resonant (13)C-(1)H probehead. Three-dimensional chemical shift imaging was used to obtain (1)H-decoupled (13)C-spectra in 96-microl voxels in about 58 min. Acquisition weighting significantly reduced signal contamination and improved image quality, with no penalty in sensitivity. As a first application, infarcted hearts were studied during perfusion with [2-(13)C]-sodium acetate. The extent of the incorporation of the (13)C-label into glutamate allows us to distinguish intact and infarcted myocardium. Chemical shift images show a homogeneous glutamate distribution in intact tissue, but a negligible amount in the infarction scar.